Bid-Ask Spread Analysis on Stock Split in Jakarta Stock Exchange - Lion Simbolon (Business and Entrepreneurial Review, 2005)
The background of this study is based on the data from Jakarta Stock Exchange as to increasing number of outstanding stocks, significant increase of value of traded stock, fluctuating volume of traded stock and the bid-ask spread as for January 2004 to March 2005. The objectives of this study is to identify the divergence of price, trade volume, and stock price volatility as well as bid-ask spread before and after the stock split; and find out the effect of price, trade volume, and stock price volatility towards spread percentage before and after the stock split. The method of this study applies correlational study to find out the degree of variation among the factors. Stock price, stock price volatility, and trade volume are classified as dependent variable and bid-ask spread is classified as independent variable. Data analysis used in this study is multiple linear regression method with the assumption that the dependent variables are not correlated or no multicollinearity is existed. This study also applied two hypothesis tests: t -test and F-test.